Analysis the Relationship of Budget Planning to Budget Absorption in Regional Device Organizations Health Department of Konawe District Islands - Dzuhri Abdullah , La Ode Muhammad; Saafi , La Ode; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2022)
Introduction: Based on data from the Regional Finance Agency of the Konawe Islands Regency in the 2019 budget year the achievement rate is 21.93%. Meanwhile, for the 2020 fiscal year, it only reached 19.31%. The problem of the level of budget absorption should be reduced if the Regional Device Organization of the Health Office of the Konawe Islands Health Office. Based on this, the researcher is interested in conducting a study on the analysis of the relationship between budget planning and budget absorption in the Regional Device Organization of the Konawe Islands District Health Office. Method: This research is quantitative using a cross sectional design, namely collecting, analyzing, and describing information and data systematically, while increasing understanding of certain phenomena. Result: There is a moderate relationship between planning and budget absorption, it is known from the results of data analysis and obtained a value of X Count or Chi Square 14,653 > from 3.84 or X table and a Phi value of 0.536, there is a moderate relationship between budget execution and budget absorption Conclusion: There needs to be an increase in periodic performance evaluations for the Regional Device Organization of the Konawe Islands District Health Office, especially regarding budget absorption, and it is necessary to improve employee performance by providing training to further deepen their work and fluency in work.